0097 Expanding Horizons: Interactive E Learning In Human Factors. (1st November 2014) - Hanson, Jacky; Selby, Ian; Hellaby, Mark; Dickinson, Mike; Pimblett, Mark
Abstract : Background: A recent concordat statement by the National Quality Board (NQB, 2013) signed by regulatory, government and healthcare organisations stated that "a wider understanding of Human Factors principles and practices will contribute significantly to improving the quality (effectiveness, experience and safety) of care of patients". Human factors (HF) are described as "enhancing clinical performance through an understanding of the effects of teamwork, task, equipment, workspace, culture and organisation on human behaviour and abilities and application of that knowledge in clinical settings" (Catchpole, 2010). The aim was to develop pre-learning material for HF development sessions for the multidisciplinary healthcare team. Methodology: The original presentation was a powerpoint slideshow, which was utilised to introduce HF in Lancashire Teaching Hospitals NHS Trust. This provided the basis for the development of an interactive e-learning package by a project team, once designed, the team reviewed and provided feedback repeatedly, and the penultimate version was placed on the website. This was piloted by experts and multiprofessional learners. The final version is on the NWSEN website and made available to organisations to host on their virtual learning environments. Results/outcomes: The module is used by a number of organisations across the UK including Royal Colleges, deaneries, individual trusts and universities, and feedback obtained. Pilot reviewers: 5 Consultants 2 trainees NW Anaesthetic trainee HF course candidates NWSEN HF working group Total number of organisations using package currently: 15 Potential impact: The development of this interactive e-learning package on HF required technical e -learning knowledge to develop an interactive platform. It has enabled HF knowledge to reach a wider audience. The package was initially conceived as a pre-learning resource before simulation sessions, however several organisations are using this as stand-alone learning for staff or trainees. A greater understanding provides the ability to improve safety and performance in the healthcare setting. References: NQB, (2013). Human Factors in Healthcare: A Concordat from the National Quality Board. Retrieved from http://www.england.nhs.uk/wp-content/uploads/2013/11/nqb-hum-fact-concord.pdf Catchpole K, McCulloch P. Human factors in critical care: towards standardised integrated human-centred systems of work. Current Opinion in Critical Care 2010;16(6):618–622 doi: 10.1097/MCC.0b013e32833e9b4b.